A (des)necessidade de criminalização da homofobia - Alves, Robson Cosme de Jesus (2013)
The present work conducts na analytical and critical-reflexive study on the criminalization of homophobia in Brazil, presented in PLC 122/2006, which tackles this issue in light of a theoretical reference based on (i) Luigi Ferrajoli’s “Legal Guarantism” theory, (ii) critical criminology and (iii) discussions on general human rights and human rights of minorities. Moreover, the study verifies the feasibility of applying criminal law as a mechanism for the protection of sexual minorities and their fundamental rights. In order to substantiate all used arguments in the study and place them beyond rhetorical argumentation, documental and statistical reference about sexual diversity and homophobia in Brazil will also be presented and analyzed – taking as an example the data published annually by the Gay Group of Bahia (Grupo Gay da Bahia) about homophobic crimes in Brazil. Furthermore, in pursuance of placing homophobia as a social phenomenon, a study was conducted in the paper “Sexual Diversity and Homophobia in Brazil – Intolerance and Respect towards Sexual Differences” (Diversidade Sexual e Homofobia no Brasil – Intolerância e Respeito às Diferenças Sociais), published by the Perseu Abramo Foundation (Fundação Perseu Abramo) through their Public Opinion Center (Núcleo de Opinião Pública), in partnership with the German Foundation Rosa Luxembourg (Rosa Luxembourg Stiftung – RLS), in which prejudice against the LGBT community is identified and measured, considering their own perception and the perception of society in general. Finally, it is worth mentioning that the present work has references from several articles, papers and books about (i) criminal law foundation and its rationality, (ii) penal expansionism, (iii) the symbolic function of penal law, (iv) compliance of constitutional penal principles and fundamental rights.